Multiproxy reconstruction of a large and deep subalpine lake's ecological history since the Middle Ages - Milan, Manuela; Salmaso, Nico; Tolotti, Monica; Bigler, C.; Guella, G. (Journal of Great Lakes Research, 2015)
Two short sediment cores collected at the deepest points of the two sub-basins of Lake Garda (Northern Italy) were radiometrically dated and analyzed for geochemistry, spheroidal carbonaceous particles, photosynthetic pigments and diatoms aimed at reconstructing the lake's ecological evolution over the last ~ 700 years, and at defining its reference conditions. Both cores showed steady dominance of small Cyclotella spp. and oligotrophic diatom-inferred lake TP concentrations from the Middle Ages until the 1960s. During the successive decades, meso- to eutraphentic elongated Fragilariaceae increased at the expense of small centrics, and diatom-inferred TP concentrations increased. Independent records of subfossil pigments revealed higher pytoplankton biomass and abundance of cyanobacteria in both lake basins since the 1990s. Trends of biological proxies and reconstructed lake TP level agree with modern limnological data collected since the 1990s. Multivariate analyses outlined lake nutrient level as the principal driver of long-term trophic and diatom evolution of Lake Garda and suggested that decadal scale climate dynamics (i.e. air temperature, East Atlantic and North Atlantic Oscillation teleconnection indices) may indirectly modulate the nutrient-driven phytoplankton evolution. The comparison of the two cores revealed that only the larger lake basin responded to major hydrological changes in the catchment during the 1940s. The study emphasizes the vulnerability of large and deep subalpine lakes towards the steadily increasing anthropogenic pressures affecting such lakes, under the present context of global warming.